2014
DOI: 10.3109/13697137.2014.929649
|View full text |Cite
|
Sign up to set email alerts
|

Maca reduces blood pressure and depression, in a pilot study in postmenopausal women

Abstract: Objective: Lepidium meyenii (Maca), a herbaceous plant, has been used for centuries for its fertility enhancing and aphrodisiac properties. In an Australian study, Maca improved anxiety and depressive scores. The effects of Maca on hormones, lipids, glucose, serum cytokines, blood pressure, menopausal symptoms and general well-being in Chinese postmenopausal women were evaluated Methods: A randomized, double-blind, placebo-controlled crossover study was conducted in 29 postmenopausal Hong Kong Chinese women. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 51 publications
3
34
0
1
Order By: Relevance
“…In a randomised, double-blind, placebocontrolled crossover study of 29 postmenopausal Hong Kong Chinese women, maca treatment did not exert hormonal or immune biological action in the small cohort of patients; however, it appeared to reduce symptoms of depression and improve diastolic blood pressure (Stojanovska et al 2014 ). Although results were comparable to previous similar published studies in postmenopausal women, there might be a cultural difference among the Chinese postmenopausal women in terms of symptom reporting.…”
Section: Clinical Studiessupporting
confidence: 61%
“…In a randomised, double-blind, placebocontrolled crossover study of 29 postmenopausal Hong Kong Chinese women, maca treatment did not exert hormonal or immune biological action in the small cohort of patients; however, it appeared to reduce symptoms of depression and improve diastolic blood pressure (Stojanovska et al 2014 ). Although results were comparable to previous similar published studies in postmenopausal women, there might be a cultural difference among the Chinese postmenopausal women in terms of symptom reporting.…”
Section: Clinical Studiessupporting
confidence: 61%
“…Although HRT has been reported to inhibit the development of NAFLD, it also results in unexpected adverse effects (Florentino et al, ; Gutierrez‐Grobe, Ponciano‐Rodríguez, Ramos, Uribe, & Méndez‐Sánchez, ; Mintziori et al, ). As HRT is controversial, the use of natural products has recently attracted more attention (Kim et al, ; Stojanovska et al, ). A phytol‐enriched diet has been reported to influence the fatty acid metabolism via PPARα‐dependent and ‐independent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Although macamides content is higher in black maca, red one enhanced the health score of human suffered from chronic mountain illness [55]. It has been shown in women that postmenopausal symptoms such as anxiety, depression and sexual dysfunction are reduced without being dependent on reproductive hormones [56,57]. Similar effects were also observed in men.…”
Section: Antioxidant Effects Of Maca As a Food Supplement In Human Numentioning
confidence: 74%
“…Some studies suggested that maca consumption is well tolerated and has no adverse effect [55]. On the contrary, some studies have reported negative effects on blood pressure [57,63,64].…”
Section: Antioxidant Effects Of Maca As a Food Supplement In Human Numentioning
confidence: 99%